Ear diseases in school going children of Sunsari and Morang districts of Nepal - Thakur, Sanjeev Kumar; Acharya, Rabin; Singh, Sanjay Kumar; Ghimire, Nisha (Journal of Chitwan Medical College, 2017)
This study was carried out to find the prevalence of ear diseases in school-going children of the Sunsari and Morang district of Eastern Nepal. This is a prospective, cross sectional, clinical study in 3729 school going children of up to 15 years of the Sunsari and Morang district of eastern Nepal done in year 2014 and 2015 AD. Informed consent was obtained. 1346 (36.09%) children had different ear ailments. Ear wax 616 (45.76%) and otitis media with effusion 226 (16.79%) were the commonest diseases found. Chronic otitis media mucosal type was found in 104 (7.73%) children. Chronic otitis media squamous 6 (0.45%), Otomycosis 155 (11.51%), otitis externa 16 (1.19%), acute Otitis media 119 (8.84%), Eustachian tube dysfunction 92 (6.84%), Perichondritis 4(0.29%), Foreign body in the ear 2 (0.15%), Preauricular sinus 2 (0.15%) and sensorineural hearing loss 4 (0.29%) were the other diseases found. Ear diseases are important health problems among school-going children of the Sunsari and Morang district of eastern Nepal. Health education,nutrition, improvement of socioeconomic status and health care facilities should be helpful in reducing the prevalence of ear diseases.